Antimalaria in-vivo activity test of ki pahit extract (Picrasma javanica) to mice infected with Plasmodium berghei - PRAPTIWI PRAPTIWI; MINDARTI HARAPINI; CHAIRUL CHAIRUL (Society for Indonesian Biodiversity, 2007)
Malaria remains as one of global health problem, in which malaria infection in the last two decades increase twice. On the other hand, the uses of plants as antimalarial sources had been known. Some plant species of Simaroubaceae have been known to have antimalarial properties. Picrasma javanica is one plant species of Simaroubaceae. In this study, P. javanica extracts was tested for antimalarial against rodent plasmodium, Plasmodium berghei in single dose (20 mg/kg BW). Leaves, fruit and stem bark extracts of P. javanica were tested to determine the extract which has the best in decreasing parasitemia, followed by variation doses test (1, 10, 100 and 1000 ppm) to determine the effectivity dose (ED50). The results showed that stem bark extract decrease parasitemia (73.89%) better than leaves (71.4%), fruit (-) extracts and chloroquin (32.35%) as positive control. The effective dose (ED50) of stem bark extract was 110.09 mg/kgBW. Phytochemical screening showed that stem bark extract of ki pahit (P. javanica) contained alkaloid, flavonoid, tannin and diterpene.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Picrasma javanica, Plasmodium berghei, ED50